Modified halloysite nanoclay as a vehicle for sustained drug delivery - Bediako, E.G.; Nyankson, E.; Dodoo-Arhin, D.; Agyei-Tuffour, B.; Łukowiec, D.; Tomiczek, B.; Yaya, A.; Efavi, J.K. (Heliyon, 2018)
This paper presents the effect of modified halloysite nanotubes on the sustained drug release mechanisms of sodium salicylate. Acid treatment and composite polymer-halloysite modification techniques were adopted in this study. After each modification, sodium salicylate drug was loaded, and in vitro release properties were evaluated and compared with the raw unmodified halloysite nanotubes. The results obtained from SEM, TEM and FTIR analyses indicate that both acid treatment and composite formation have no effect on the tubular structure and morphology of halloysite. However, modification of the halloysite nanotubes did influence the drug release rate. In the acid treatment modification, there was an improved loading of sodium salicylate drug which resulted in the sustain release of large amount of the sodium salicylate. In the polymer/halloysite composite formation, a consistent layer of polymer was formed around the halloysite during the composite formation and thus delayed release providing sustained release of sodium salicylate drug over a longer period of time as compared to the acid treated and unmodified halloysite. The results from the invitro release were best fitted with the Higuchi and the Koresymer-Peppas models.
Keywords: Biomedical engineering; Materials science; Nanotechnology